PERBANDINGAN HASIL BELAJAR MATA PELAJARAN FIKIH ANTARA PESERTA DIDIK YANG AKTIF ORGANISASI DAN PESERTA DIDIK YANG TIDAK AKTIF ORGANISASI - Ariani, Yusi; Handoko, Indra Dwi; Kusnawan, Wawan (THORIQOTUNA: Jurnal Pendidikan Islam, 2022)
The purpose of this research is to compare the learning outcomes of fiqh subjects between students who are active in organizations and students who are not active in organizations at MTs Serba Bakti Suryalaya Tasikmalaya.The research method used is a comparative analysis method with a quantitative approach. The population is all students of MTs Serba Bakti Suryalaya Tasikmalaya as many as 532 people. While the sample is 193 respondents class VIII A- VIII G. The sampling technique used is purposive sampling. While the data collection techniques used are observation, documentation and interviews.The results of data processing showed that the learning outcomes of fiqh subjects of students who were active in organizations at MTs Serba Bakti were very good (Me = 178.23 which was between 173.08 - 178.44 on the interpretation scale with very good classification). And the learning outcomes of fiqh subjects that are not active in the organization are good (Me=164.80, which is between 161.68 – 169.02 on the interpretation scale with good classification). As for the comparison of the two variables, there is a significant difference in the learning outcomes of active and inactive students in the organization. Namely, the results of the "t" test are t-count 7.34 and t-table with a significant level of 5% of 1.652, so the result of t-count is greater than t-table or 7.34> 1.652, therefore the alternative hypothesis is accepted.